2002
DOI: 10.1046/j.1523-1755.2002.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A-induced hypercalciuria in calbindin-D28k knockout and wild-type mice

Abstract: Calbindin-D28k KO mice have diet-dependent hypercalciuria and a lower bone turnover rate. CsA treatment suppresses the expression of calbindin-D28k in mice, but has no effects on ECaC and alpha1G gene expression at the mRNA level. The pathogenesis of CsA-induced hypercalciuria involves both down-regulation of calbindin-D28k with subsequent impaired renal calcium reabsorption and CsA-induced high turnover bone disease. Additionally, our results suggest that mechanism(s) independent of calbindin-D28k within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 26 publications
7
39
0
2
Order By: Relevance
“…We then treated TPTX, PTH-supplemented rats with an antibone-resorptive agent (2.5 μg pamidronate.g BW -1 , daily for 4 days prior to the experiment); this treatment significantly inhibits bone resorption in rats and mice as validated in previous studies (9,12,13). As shown in Figure 4, at baseline, both groups of rats exhibited the same blood ionized Ca concentration and urinary Ca excretion.…”
Section: Figurementioning
confidence: 77%
“…We then treated TPTX, PTH-supplemented rats with an antibone-resorptive agent (2.5 μg pamidronate.g BW -1 , daily for 4 days prior to the experiment); this treatment significantly inhibits bone resorption in rats and mice as validated in previous studies (9,12,13). As shown in Figure 4, at baseline, both groups of rats exhibited the same blood ionized Ca concentration and urinary Ca excretion.…”
Section: Figurementioning
confidence: 77%
“…Some studies show that these genes are regulated by calcium but not 1,25-dihydroxyvitmain D 3 in mice lacking VDR (38), whereas others show that they are modulated by both calcium and 1,25-dihydroxyvitmain D 3 in WT mice (39) and in mice lacking 1␣-hydoxylase (5). A previous report also shows that levels of TRPV5 are not altered in CaBP-D28k(Ϫ/Ϫ) mice (32). Here we demonstrate that expression of both TRPV5 and TRPV6 is not changed in CaBP-D28k(Ϫ/Ϫ) mice but down-regulated by about the same magnitude in both VDR(Ϫ/Ϫ) and double KO mice.…”
Section: Table II Physiological Parameters Of 2-month Old Wt Cabp-d2mentioning
confidence: 83%
“…The bone phenotype, presumably normal, was not investigated when the KO mice were first reported. More recent studies reported that CaBP-D28k(Ϫ/Ϫ) mice fed a 1% calcium diet had higher urinary calcium excretion and a lower bone turnover rate than WT mice, even though their serum calcium levels and intestinal CaBP-D9k expression were normal (31,32). In theory, to maintain a calcium balance, these mutant mice need to have increased intestinal calcium absorption and/or higher bone turnover, which is contradictory to the normal intestinal CaBP-D9k levels and lower bone turnover seen in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…CsA has been previously shown to enable repeated administration of monoclonal antibody therapy in patients by reducing the HAMA response (Ledermann et al, 1988;Weiden et al, 1994). Notably, the amount of CsA administered in the in vivo experiments in rats was lower, based on several publications (Palomero et al, 2001;Lee et al, 2002), that the doses commonly used in patients for immunosupression, as calculated from commonly used guidelines for conversion of doses between different species (www.fda.gov/Cber/ gdlns/dose.htm). However, whether CsA can inhibit the antibody formation to the IT will be studied in a clinical trial in 2009 in our clinical trials unit.…”
Section: Discussionmentioning
confidence: 99%